Mutations in the Human AAA+ Chaperone p97 and Related Diseases - Tang, Wai Kwan; Xia, Di (Frontiers in Molecular Biosciences, 2016)
A number of neurodegenerative diseases have been linked to mutations in the human protein p97, an abundant cytosolic AAA+ (ATPase associated with various cellular activities) ATPase, that functions in a large number of cellular pathways. With the assistance of a variety of cofactors and adaptor proteins, p97 couples the energy of ATP hydrolysis to conformational changes that are necessary for its function. Disease-linked mutations, which are found at the interface between two main domains of p97, have been shown to alter the function of the protein, although the pathogenic mutations do not appear to alter the structure of individual subunit of p97 or the formation of the hexameric biological unit. While exactly how pathogenic mutations alter the cellular function of p97 remains unknown, functional, biochemical and structural differences between wild-type and pathogenic mutants of p97 are being identified. Here, we summarize recent progress in the study of p97 pathogenic mutants.